2006
DOI: 10.2166/wpt.2006.033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Estrogenic Hormones in Natural Waters, Wastewater and Sludge. Results from the First International Round Robin Test

Abstract: This paper reports the results from the first international round robin test on estrogenic hormones in 5 types of matrices including groundwater, surface water, influent and effluent wastewater and a freeze dried wastewater plant sludge. The 14 participating laboratories used a wide variety of analytical techniques comprising different extraction, cleanup and separation-detection procedures. The latter comprised GC/MS, GC/MS/MS, LC/MS, LC-TOF MS, LC/MS/MS with ESI or APPI interfaces, and a rather uncommon LC-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
3
1
0
Order By: Relevance
“…All steroid FN rates increased in the SW comparison, most likely because the spike levels were lowered for this round and the matrix was more complex. These results agree with previous work that suggests steroidal analysis may be difficult at concentrations ∼5 ng/L, depending on whether single- or triple-quadrupole instruments were used. The elevated false positive and false negative rates of some analytes underscore the susceptibility of samples to blank contamination and/or improper determination of detection/quantification levels for analysis at low ng/L levels.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…All steroid FN rates increased in the SW comparison, most likely because the spike levels were lowered for this round and the matrix was more complex. These results agree with previous work that suggests steroidal analysis may be difficult at concentrations ∼5 ng/L, depending on whether single- or triple-quadrupole instruments were used. The elevated false positive and false negative rates of some analytes underscore the susceptibility of samples to blank contamination and/or improper determination of detection/quantification levels for analysis at low ng/L levels.…”
Section: Resultssupporting
confidence: 92%
“…In contrast with previous studies, , no trends or correlations were found between overall bias and experience or extraction technique; however, methods employing LC–MS/MS were able to achieve overall biases of <10% for most compounds (Table ), while GC/MS methods were consistently in the lower 50th percentile. These conclusions agree with a previous interlaboratory comparison study but disagree with two others, , although one of these studies found that GC/MS led to the presence of more outliers . In most cases, a single ionization technique was shared by all methods within a particular instrumental class (e.g., all EI for GC/MS vs all ESI– for LC–MS/MS), with the notable exception being the steroids.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations